Eye See What You See: Exploring How Bi-Directional Augmented Reality Gaze Visualisation Influences Co-Located Symmetric Collaboration - Jing, Allison; May, Kieran; Lee, Gun; Billinghurst, Mark (Frontiers in Virtual Reality, 2021)
Gaze is one of the predominant communication cues and can provide valuable implicit information such as intention or focus when performing collaborative tasks. However, little research has been done on how virtual gaze cues combining spatial and temporal characteristics impact real-life physical tasks during face to face collaboration. In this study, we explore the effect of showing joint gaze interaction in an Augmented Reality (AR) interface by evaluating three bi-directional collaborative (BDC) gaze visualisations with three levels of gaze behaviours. Using three independent tasks, we found that all BDC visualisations are rated significantly better at representing joint attention and user intention compared to a non-collaborative (NC) condition, and hence are considered more engaging. The Laser Eye condition, spatially embodied with gaze direction, is perceived significantly more effective as it encourages mutual gaze awareness with a relatively low mental effort in a less constrained workspace. In addition, we suspect that by offering another virtual representation that compensates for verbal descriptions and hand pointing, BDC gaze visualisations can encourage more conscious use of gaze cues coupled with deictic references during co-located symmetric collaboration. We provide a summary of the lessons learned, limitations of the study, and directions for future research.